Memory-related hippocampal brain-derived neurotrophic factor activation pathways from repetitive transcranial magnetic stimulation in the 3xTg-AD mouse line - M. Windy McNerney; Eric P. Kraybill; Sindhu Narayanan; Fatemeh S. Mojabi; Vaibhavi Venkataramanan; Alesha Heath (Experimental Gerontology, 2023)
Alzheimer's disease is associated with a loss of plasticity and cognitive functioning. Previous research has shown that repetitive transcranial magnetic stimulation (rTMS) boosts cortical neurotrophic factors, potentially addressing this loss. The current study aimed to expand these findings by measuring brain-derived neurotrophic factor (BDNF), its downstream hippocampal signaling molecules, and behavioral effects of rTMS on the 3xTg-AD mouse line. 3xTg-AD (n = 24) and B6 wild-type controls (n = 26), aged 12 months, were given 14 days of consecutive rTMS at 10 Hz for 10 min. Following treatment, mice underwent a battery of behavioral tests and biochemical analysis of BDNF and its downstream cascades were evaluated via Western blot and ELISA. Results showed that brain stimulation did improve performance on the Object Place Task and increased hippocampal TrkB, ERK, and PLCγ in 3xTg-AD mice with minimal effects on wild-type mice. There was no significant difference in the levels of AKT and Truncated TrkB (TrkB.T1) between treatment and sham. Thus, rTMS has the potential to provide an efficacious non-invasive therapy for the treatment of Alzheimer's disease through activation of neurotrophic factor signaling.